Strategic ambiguity : alive and well - Sworn, Hannah Elyse (2022)
President Joe Biden’s recent comments regarding Taiwan do not depart from Washington’s longstanding policy of strategic ambiguity, but rather reflect its adaptation to balance Chinese actions in the Taiwan Strait.